Injurious Loading of Articular Cartilage Compromises Chondrocyte Respiratory Function. Issue 3 (March 2016) - Coleman, Mitchell C.; Ramakrishnan, Prem S.; Brouillette, Marc J.; Martin, James A.
Abstract : Objective: To determine whether repeatedly overloading healthy cartilage disrupts mitochondrial function in a manner similar to that associated with osteoarthritis (OA) pathogenesis. Methods: We exposed normal articular cartilage on bovine osteochondral explants to 1 day or 7 consecutive days of cyclic axial compression (0.25 MPa or 1.0 MPa at 0.5 Hz for 3 hours) and evaluated the effects on chondrocyte viability, ATP concentration, reactive oxygen species (ROS) production, indicators of oxidative stress, respiration, and mitochondrial membrane potential. Results: Neither 0.25 MPa nor 1.0 MPa of cyclic compression caused extensive chondrocyte death, macroscopic tissue damage, or overt changes in stress–strain behavior. After 1 day of loading, differences in respiratory activities between the 0.25 MPa and 1.0 MPa groups were minimal; however, after 7 days of loading, respiratory activity and ATP levels were suppressed in the 1.0 MPa group relative to the 0.25 MPa group, an effect prevented by pretreatment with 10 m M N ‐acetylcysteine. These changes were accompanied by increased proton leakage and decreased mitochondrial membrane potential, as well as by increased ROS formation, as indicated by dihydroethidium staining and glutathione oxidation. Conclusion: Repeated overloading leads to chondrocyte oxidant‐dependent mitochondrial dysfunction. This mitochondrial dysfunction may contribute to destabilization of cartilage during various stages of OA in distinct ways by disrupting chondrocyte anabolic responses to mechanical stimuli.